Festival Research in Croatia - Škrbić Alempijević, Nevena (2008)
There is a long tradition of the involvement of Croatian ethnologists in festivals. This engagement has been twofold: ethnologists have carried out scientific research, but also their have been involved in organization of such manifestations. The emphasis has been placed on festivals re-enacting traditional rural patterns. The development of ethnological institutions and the organization of folklore festivals have been closely interwoven. Since stress was placed on heritage, and especially on rural folklore manifestations, the research was conducted only fragmentary. In the ethnological discourse festivals are still sometimes depicted as dance and music presentations. This paper's aim is to address this attitude.